Correction: Wiped out by an earthquake? The 'extinct' Taiwanese swallowtail butterfly (Lepidoptera, Papilionidae) was morphologically and genetically distinct. - Vazrick Nazari; Shen-Horn Yen; Yu-Feng Hsu; Galina Shapoval; Nazar Shapoval; Valentina Todisco (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0310318.].